A revision of Physotarsus Townes (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with description of 18 new species - Zhaurova, Kira; Wharton, Robert (Zootaxa, 2009)
The species of Physotarsus Townes are revised. Physotarsus is expanded to include 18 new species: P. albus Zhaurova, n. sp. (Brazil), P. claviger Zhaurova, n. sp. (Argentina), P. concavus Zhaurova, n. sp. (USA & Mexico), P. cordatus Zhaurova, n. sp. (USA), P. emarginatus Zhaurova, n. sp. (USA), P. flavipennis Zhaurova, n. sp. (USA), P. foveatus Zhaurova, n. sp. (USA & Mexico), P. gineus Zhaurova, n. sp. (USA), P. glabellus Zhaurova, n. sp. (Brazil), P. jamesi Zhaurova, n. sp. (Dominica), P. leucohypopygus Zhaurova, n. sp. (Brazil), P. luteus Zhaurova, n. sp. (Mexico), P. melipennis Zhaurova, n. sp. (USA), P. melotarsus Zhaurova, n. sp. (USA), P. niveus Zhaurova, n. sp. (Brazil), P. oculatus Zhaurova, n. sp. (Brazil), P. tonicus Zhaurova, n. sp. (USA), and P. truncatus Zhaurova, n. sp (USA). Physotarsus davidi Gauld, 1997 is treated as a junior subjective synonym of P. varicornis (Cameron, 1886) and a lectotype is designated for the latter. Physotarsus fabioi Gauld, 1997 is removed from the Scolobatini and left incertae sedis in the Ctenopelmatinae. A key to all known species of Physotarsus, and redescriptions of all previously described species are also provided. With 25 valid species, Physotarsus is now the largest genus in the Scolobatini.